Understanding pathophysiology - Huether, Sue E.; McCance, Kathryn L;Brashers, Valentina L. ;Rote, Neal S. (St. Louis, Missouri : Elsevier Science, 2012)
Learn the essential concepts of pathophysiology and stay up to date on treatments, manifestations, and mechanisms of disease with Understanding Pathophysiology, 5th Edition. Filled with vibrant illustrations and complemented by online resources that bring pathophysiology concepts to life, this easy-to-read text delivers the latest, most accurate information on the disease process across the lifespan, giving you the fundamental knowledge you need to move forward in your nursing education.
Cellular biology Genes and genetic diseases Altered cellular and tissue biology Fluids and electrolytes, acids and bases Innate immunity: inflammation and would healing Adaptive immunity Infection and defects in mechanisms of defense Stress and disease Biology, clinical manifestations, and treatment of cancer Cancer epidemiology Cancer in children Structure and function of the neurologic system Pain, temperature, sleep and sensory function Alterations in cognitive systems, cerebral hemodynamics and motor function Disorders of the central and peripheral nervous systems and neuromuscular junction Alterations of neurologic function in children Mechanisms of hormonal regulation Alterations of hormonal regulation Structure and function of the hematologic system Alterations of hematologic function Alterations of hematologic function in children Alterations of the reproductive systems, including sexually transmitted infections Structure and function of the digestive system Alterations of digestive function Alterations of digestive function in children Structure and function of the musculoskeletal system Alterations of musculoskeletal function Alterations of digestive function in children Structure and function of the musculoskeletal system Alterations of musculoskeletal function Alterations of musuloskeletal function in children Alterations of musculoskeletal function Alterations of musculoskeletal function in children Structure, function, and disorders of the integument Alterations of the integument in children
Includes bibliographical references and index.
Keywords: PATHOLOGY